Social Leaders or Political Followers? : Institutional Accreditation and the Rise of State Regulations (Higher Education Politics and Economics, 2025)
This paper traces the history of higher education accreditation before considering how institutional leaders should respond to current state-based attempts that challenge traditional values related to accreditation. Historical higher education accreditation regimes are changing. For example, the Trump-led Department of Education (ED) introduced new rules resulting in the end of regional boundaries related to accreditation and a potential influx of new institutional gatekeepers. Since then, some states have attempted to break up the “higher-education cartels,” by requiring institutions to change institutional accreditors every reaffirmation cycle, threatening university policies related to shared governance and academic freedom, and exerting inappropriate political control. Against this backdrop, the ED has adopted new policies and recently announced a new round of negotiated rule-making related to accreditation. This paper concludes by considering Douglas’s political determinist hypothesis using case studies related to state actions impacting accreditation and how higher education leaders should respond (2021).